1988
DOI: 10.1111/j.1745-4557.1988.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Restructured Pork With Texture Variation

Abstract: Muscles were excisedfrom the shoulders of U. S. No. I pork carcasses within Ih postmortem. Samples were flaked as; small (head opening = 3.otnm), medium (head opening = 6.Imm) and large (head opening = 9.9mm) with an Urschel Comitrol 3600. Samples were formulated with 1.0 NaCl and 0.2% sodium tripolphosphate rSTP), converted into 19 mm thick restructured chops and packaged. Subjective evaluations were conducted after 5 and 56 days of frozen storage for color, cohesiveness, muscle cut resemblance, overall appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…However, Sen and Karim (2003) reported that meat particle size reduction had no significant effect on acceptability of restructured mutton steaks. Similarly, Marriot et al (1986) reported that particle size had no effect on flavour and juiciness of restructured pork, but tenderness decreased as particle size increased from 3 to 9.9 mm. Meat chunk size of 2-3 cm was selected for further studies due to higher product yield and significantly better appearance and overall acceptability of the products.…”
Section: Sensory Evaluationmentioning
confidence: 93%
“…However, Sen and Karim (2003) reported that meat particle size reduction had no significant effect on acceptability of restructured mutton steaks. Similarly, Marriot et al (1986) reported that particle size had no effect on flavour and juiciness of restructured pork, but tenderness decreased as particle size increased from 3 to 9.9 mm. Meat chunk size of 2-3 cm was selected for further studies due to higher product yield and significantly better appearance and overall acceptability of the products.…”
Section: Sensory Evaluationmentioning
confidence: 93%
“…Marriott et al (1987) reported particle size of restructured chops had no effect on the resemblance of these samples to whole muscle cuts; however, none of the samples compared looked like whole muscle cuts. Furthermore, restructured chops manufactured from larger fl ake particles were less tender and contained more connective tissue than those samples made from smaller particles.…”
Section: Particle Size Reductionmentioning
confidence: 56%
“…Furthermore, restructured chops manufactured from larger fl ake particles were less tender and contained more connective tissue than those samples made from smaller particles. Some researchers have reported size of meat pieces had no affect on juiciness of the restructured product (Marriott et al, 1987;Raharjo et al, 1995). Boles and Shand (1998), however, found juiciness of steakettes made from fl aked meat was liked less by consumer panelists than steakettes made from ground meat.…”
Section: Particle Size Reductionmentioning
confidence: 95%
See 2 more Smart Citations